The fauna of Africa and Asia described by Christian travelers between the thirteenth and fifteenth centuries - Gonçalves, Rafael Afonso (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
During the thirteenth, fourteenth and fifteenth centuries, a considerable number of European Christians traveled to destinations far beyond the limits of Christianity, such as India, China, Mongolia and the African coasts. To tell their countrymen what they had seen in those unknown lands, many of these travelers wrote their memories and impressions. Among the many descriptions on these reports, the ones about the animals that inhabited those lands – some completely unknown, others familiar to them – draw attention. The aim of this brief research note is to present the main options and challenges of an ongoing research project, whose goal is to promote an accurate cataloging of the species mentioned by travelers. Among the data that will be collected, the catalog seeks to identify how those animals were named and classified, in what places they were commonly found, what were their main characteristics and behaviors and how they were used by natives.
Keywords: Medieval History; Animals; Travels and travelers; Environment; East; Africa